Pemberdayaan Masyarakat Melalui Bank Sampah Sebagai Strategi Pengelolaan Sampah Dan Peningkatan Ekonomi - Eva Rolia; Agus Sutanto; Fajri Arif Wibawa; Farida Ramalida; Faisal Nur Arifin; Gita Angelita; Intan Utami; Muhammad Fiqih Akbar Bayhaqi; Herlisa Hafizah Putri (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Community empowerment through the Waste Bank program in Rejoagung Village aims to address waste management issues while creating environmentally based economic opportunities. This community service program aims to analyze the impact of the establishment of a Waste Bank on community economic empowerment, especially women, through processing waste into value-added products. The implementation method of the service is in 3 (three) stages: the preparation stage, the implementation stage, and the evaluation stage. The results of the service show that the Waste Bank program has succeeded in increasing community environmental awareness, strengthening institutional capacity, and providing economic opportunities through recycled products such as handicrafts. Training in technical, managerial, and product marketing skills also plays a role in increasing family income, especially for members of the Family Welfare Movement (PKK) and the Women's Farmers Group (KWT). In conclusion, the success of the Waste Bank program in Rejoagung Village shows great potential in environmentally based economic empowerment, but strengthening management and marketing capacity is needed to ensure the program's sustainability.ABSTRAKPemberdayaan masyarakat melalui program Bank Sampah di Desa Rejoagung bertujuan untuk mengatasi masalah pengelolaan sampah sekaligus menciptakan peluang ekonomi berbasis lingkungan. Pengabdian ini bertujuan untuk menganalisis dampak pembentukan Bank Sampah terhadap pemberdayaan ekonomi masyarakat, khususnya perempuan, melalui pengolahan sampah menjadi produk bernilai tambah. Metode pelaksanaan pengabdian yakni dengan 3 (tiga) tahapan yakni tahap persiapan, tahap pelaksanaan dan tahap evaluasi. Hasil pengabdian menunjukkan bahwa program Bank Sampah berhasil meningkatkan kesadaran lingkungan masyarakat, memperkuat kapasitas kelembagaan, serta memberikan peluang ekonomi melalui produk daur ulang seperti kerajinan tangan. Pelatihan keterampilan teknis, manajerial, dan pemasaran produk turut berperan dalam meningkatkan pendapatan keluarga, terutama bagi anggota PKK dan Kelompok Wanita Tani (KWT). Kesimpulannya, keberhasilan program Bank Sampah di Desa Rejoagung menunjukkan potensi besar dalam pemberdayaan ekonomi berbasis lingkungan, namun diperlukan penguatan kapasitas pengelolaan dan pemasaran untuk memastikan keberlanjutan program.